1995
DOI: 10.1177/095632029500600606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant-Derived Polysaccharides on Murine Cytomegalovirus and Encephalomyocarditis Virus Infections in Mice

Abstract: SummaryPolysaccharides from three plant species, Astragalus brachycentrus (AV222), Astragalus echidnaeformis (AV224) and Sterculia urens (AV223), which are devoid of in vitro antiviral activity, were evaluated in mouse models of murine cytomegalovirus and encephalomyocarditis virus infections. AV223 and AV224 were very potent agents, protecting mice from mortality at intraperitoneal doses between 3.2 and 100 mg kg-1 day-1 treatments. Treatment with compounds needed to be started one day prior to virus inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We previously demonstrated that these As tragalus polysaccharides also prevented mor tality in mice infected with murine cytomega lovirus and encephalomyocarditis virus [7], Stimulation of the intrinsic antiviral activity of macrophages by Corynebacterium parvum was shown to protect mice from an otherwise lethal challenge of encephalomyocarditis vi rus [25]. Interferon induction is the most common mode of antiviral action of biologi cal response modifiers [24], but not in the case of the Astragalus polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that these As tragalus polysaccharides also prevented mor tality in mice infected with murine cytomega lovirus and encephalomyocarditis virus [7], Stimulation of the intrinsic antiviral activity of macrophages by Corynebacterium parvum was shown to protect mice from an otherwise lethal challenge of encephalomyocarditis vi rus [25]. Interferon induction is the most common mode of antiviral action of biologi cal response modifiers [24], but not in the case of the Astragalus polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that these tragacanthin polysaccharides, when in jected into mice, can prevent mortality in duced by murine cytomegalovirus (a herpes virus) and encephalomyocarditis virus (a picomavirus) [7], In this report we describe the antiviral effects of two tragacanthin polysac charides on Punta Toro virus (PTV) infec tions in mice. PTV is a phlebovirus of the Bunyaviridae family of viruses which we have used as a model for the highly hazardous Rift Valley fever and hantavirus infections in studying antiviral agents and biological re sponse modifiers [8,9], Due to the extreme Tragacanthin Polysaccharidesand PTV Infections severity of these infections in man [10,11], there is a need for effective antiviral treat ments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astragalus species are recommended for all types of immune disorders caused by poor or low immune system function (8-11). The pharmacological activity of the root extract of this plant extract includes antiviral and antibacterial activity, liver protection, and anticancer activity, as well as blood pressure lowering and diuretic effects (12)(13)(14)(15)(16)(17)(18)(19). In addition, Astragalus species contain saponins, polysaccharides, and phenolics, while the toxic compounds include imidazoline alkaloids, nitro toxins, and selenium derivatives (20).The lipids of legumes have not been investigated in any great detail because of the low lipid content (21-23).…”
mentioning
confidence: 99%
“…[3][4][5] Chemical studies on Astragalus saponins have reported the presence of cycloartane-type triterpenoid glycosides which were found to exert biological activities (e.g. anti-inflammatory, analgesic, diuretic, hypotensive and sedative effects).…”
mentioning
confidence: 99%